Effect of straw amendment modes on soil organic carbon, nitrogen sequestration and crop yield on the North‐Central Plain of China. (12th April 2019) - Zhao, Huili; Ning, Peng; Chen, Yanlong; Liu, Jifei; Ghaffar, Shar A.; Xiaohong, Tian; Shi, Jianglan
Abstract: We quantified the effects of different straw return modes on soil organic carbon (SOC), total nitrogen content (TN) and C:N ratios in a wheat/maize double‐cropping agricultural system by analysing their content in different soil aggregate sizes and density fractions under four modes of straw return: (a) no return/retention of wheat and maize straw (Control); (b) retention of long wheat stubble only (Wheat Stubble); (c) retention of long wheat stubble and return of chopped maize straw (Mixed); and (d) return of chopped wheat and maize straw (Both Chopped). The Mixed and Both Chopped straw return modes produced the highest crop yields. Relative to the Control, SOC stock was 9.6% greater with the Mixed treatment and 14.5% greater with the Both Chopped treatment, whereas the Wheat Stubble treatment had no effect on SOC. Mixed and Both Chopped significantly enhanced TN stock relative to the Wheat Stubble and Control treatments. Compared with the Control, the Mixed and Both Chopped treatments increased the mass proportions of large macroaggregates and reduced the silt plus clay fraction; Mixed and Both Chopped caused a significant increase in SOC and TN in large and small macroaggregates; the Mixed treatment significantly increased SOC content in the coarse and fine intra‐aggregate particulate organic matter (iPOM) density fractions of large macroaggregates, whereas Both Chopped increased SOC in the coarse iPOM, fine iPOM and mineral‐associated organic matter (mSOM) density fractions of both large and small macroaggregates; and Mixed and Both Chopped enhanced TN content in coarse iPOM and fine iPOM within small macroaggregates. Although the Mixed treatment was slightly less effective at improving C sequestration in agricultural fields than the Both Chopped treatment, the Mixed treatment may nonetheless be the optimal plant residue management mode in terms of minimizing time and labour due to its ability to improve soil structure, maintain organic carbon levels and provide a means of sustainable crop production in intensive wheat/maize double‐cropping systems.